Territories (Re)signified of indigenous communities in Conservation Unis of the Lower Rio Negro – Am and the adoption of tourism as an income alternative - Dias, Luana Cristina dos Santos; Cruz, Jocilene Gomes da (Revista Turismo em Análise, 2020)
In recent years, the growth of tourist activities developed by indigenous communities in the region of Baixo Rio Negro, state of Amazonas, has impacted communities socially, culturally and economically. This scenario originates due to the adoption of tourism as a means by which the indigenous people can supply their material and symbolic needs. In this article, the main objective was to analyze the tourist activity adopted by indigenous communities as an alternative to income in view of the limits of land use in a Conservation Unit (UC), in the Lower Rio Negro region, and as specific objectives: to know the strategies of the Tatuyo community, related to the use of the territory and through tourism; apprehend the dynamics of tourism structured by the community and the “place” of indigenous culture in the activity. In order to reflect on this scenario and make some contributions, the article raises relevant issues in the context of Amazonian tourism: the displacement of indigenous peoples from their lands to the surroundings of the capital of Amazonas (Manaus), the creation of indigenous communities in UC Sustainable Use and tourism, particularly in four indigenous communities, called Núcleo Diakuru and Aldeia Tuyuka (Tupé Reserve), Cipiá Community and Tatuyo Community (Puranga Conquista Reserve). The methodological path involves bibliographic, documentary and field research. The data obtained show the efforts of the communities to obtain income through cultural presentations (dances, songs and customs), however, the developed tourist activity and the relations with social agents and agencies, directly and indirectly involved in the activity, cause asymmetric relationships , power struggle and, therefore, an unsustainable “model” for communities, both due to the negative impacts on culture and on the territory.